Analysis of Oil Content and Diatom Abundance in Coastal Waters of Medan Kota Belawan North Sumatera - Situmorang, Herlin Margaretha; Amin, Bintal; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in May 2014 in Medan Kota Belawan coastal waters. The aim of this research was to analyze the oil contents and diatom abundance as well as their correlation during high and low tide. Samples of sea water for oil and diatom analysis were collected from 4 stations. The analysis of oil content as well as identification and quantification of diatom were carried out in Marine Chemistry Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau in Pekanbaru. The results of the study showed that the highest oil content was found during the high tide in Station 1 (0.322 ppm) and the lowest was at Station 4 (0.040 ppm). Diatoms that were found in the surface waters of Medan Kota Belawan coastal water comprising of 18 species. Nitzschia scrianata was the species with the highest abundance (3640.73 cells/l). The diatom abundance was found to be highest during high tide in Station 4 (1213.58 cells/l) and the lowest was during low tide in Station 1 (360.80 cells/l). Oil content with diatom abundance showed a weak negative correlation (Y = 639,7-971,1x ; R2 = 0.146 ; r = 0.382) at high tide while at low tide Y = 520.7-1370.0x ; R2 = 0.115 ; r = 0.339 which mean that increasing oil content will decrease the abundance of diatoms in Medan Kota Belawan coastal waters.Keywords : Belawan Coastal Waters, oil, diatoms and tide